Case report: detection of multiple sporadic gastrointestinal stromal tumors by dual-time 18 F-FDG PET/CT - Li, Chuan; Li, Wenxin; Shang, Maocai; Wang, Pan; Hu, Xianwen (Frontiers in Oncology, 2024)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors affecting the gastrointestinal tract. Typically, GISTs are solitary; however, in rare cases, they may be multiple and appear in one or more organs. Multiple GISTs can appear in familial GISTs, children, or certain tumor syndromes such as neurofibromatosis type 1, Carney syndrome, and Carney-Stratakis syndrome. However, the diagnosis of primary multiple sporadic GISTs is often more difficult than that of these diseases. Herein, we report a case of multiple primary sporadic GISTs in a 64-year-old man, affecting the abdominal cavity and retroperitoneum, as identified through dual-time point positron emission tomography (PET) with 18 F-labeled fluoro-2-deoxyglucose ( 18 F-FDG) and computed tomography ( 18 F-FDG PET/CT). Notably, the dual-time-point PET/CT revealed the migration of masses near the lower abdomen into the abdominal cavity. Furthermore, a significant increase in radioactive uptake of the mass 3 h after 18 F-FDG injection compared with that 1 h after injection may be an important cue for its diagnosis.